2016
DOI: 10.1007/s40096-016-0186-9
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation based on meshless technique to study the biological population model

Abstract: A kind of spectral meshless radial point interpolation method is proposed to degenerate parabolic equations arising from the spatial diffusion of biological populations and satisfactory agreements is archived. This method is based on collocation methods with mesh-free techniques as a background. In contrast to the finite-element method and those meshless methods based on Galerkin weak form, such as element-free Galerkin, there is no integration tools in this approach. Furthermore, some numerical experiments ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…For example, some recent simulation studies can be found in [1,18]. Abbasbandy and Shivanian [1] used numerical simulation based on meshless technique to study the biological population model.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, some recent simulation studies can be found in [1,18]. Abbasbandy and Shivanian [1] used numerical simulation based on meshless technique to study the biological population model.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…For example, some recent simulation studies can be found in [1,18]. Abbasbandy and Shivanian [1] used numerical simulation based on meshless technique to study the biological population model. Vajargah and Shoghi [18] used quasi-Monte Carlo method in prediction of total index of stock market and value at risk.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…The spatial diffusion of some biological species is described by nonlinear partial differential equations. In the last years, various numerical powerful methods have been applied to get the solutions of general degenerate parabolic equations, such as collocation methods with mesh-free technique [2], variational iteration method [10], Adomian decomposition method (ADM) [1,13], homotopy perturbation method [8,9], homotopy analysis Sumudu transform method [12], etc.…”
Section: Introductionmentioning
confidence: 99%
“…A. Shirzadi et al considered the same problem in both weak convection coefficients and convection dominant cases and applied meshless local Petrov‐Galerkin (MLPG) method to obtain better results but MLPG is time consuming as the result of determining shape parameter and calculating integration around each nodal point, the readers are referred to the Refs. to survey meshless methods. Z. J. Fu et al have considered the problem (1)–(4) and proposed Laplace transformed boundary particle method to solve it effectively.…”
Section: Introductionmentioning
confidence: 99%